Long non-coding RNA PAXIP1-AS1 facilitates cell invasion and angiogenesis of glioma by recruiting transcription factor ETS1 to upregulate KIF14 expression - Xu, Haiyang; Zhao, Guifang; Zhang, Yu; Jiang, Hong; Wang, Weiyao; Zhao, Donghai; Yu, Hongquan; Qi, Ling (Journal of experimental & clinical cancer research, 2019)
Gliomas are common life-threatening cancers, mainly due to their aggressive nature and frequent invasiveness and long non-coding RNAs (lncRNAs) are emerging as promising molecular targets. Therefore, we explored the regulatory mechanisms underlying the putative involvement of the lncRNA PAX-interacting protein 1- antisense RNA1/ETS proto-oncogene 1/kinesin family member 14 (PAXIP1-AS1/ETS1/KIF14) axis in glioma cell invasion and angiogenesis. Firstly, we identified differentially expressed lncRNA PAXIP1-AS1 as associated with glioma based on bioinformatic data. Then, validation experiments were conducted to confirm a high expression level of lncRNA PAXIP1-AS1 in glioma tissues and cells, accompanied by upregulated KIF14. We further examined the binding between lncRNA PAXIP1-AS1, KIF14 promoter activity, and transcription factor ETS1. Next, overexpression vectors and shRNAs were delivered to alter the expression of lncRNA PAXIP1-AS1, KIF14, and ETS1 to analyze their effects on glioma progression in vivo and in vitro. LncRNA PAXIP1-AS1 was mainly distributed in the nucleus of glioma cells. LncRNA PAXIP1-AS1 could upregulate the KIF14 promoter activity by recruiting transcription factor ETS1. Overexpression of lncRNA PAXIP1-AS1 enhanced migration, invasion, and angiogenesis of human umbilical vein endothelial cells in glioma by recruiting the transcription factor ETS1 to upregulate the expression of KIF14, which was further confirmed by accelerated tumor growth in nude mice. The key findings of this study highlighted the potential of the lncRNA PAXIP1-AS1/ETS1/KIF14 axis as a therapeutic target for glioma treatment, due to its role in controlling the migration and invasion of glioma cells and its angiogenesis.